Efeitos da variação da tarifa de energia elétrica sobre a inflação brasileira: 1996 - 2015 - Castro, Andressa Porto (2017)
In Brazil, the inflation targeting system has been adopted since 1999, with inflation measured through the Extended Consumer Price Index (IPCA), which in its basket of goods has products with free and administered prices. Inflation in recent years in Brazil can be explained as an inflation of costs caused by supply shocks, as well as an inertial component inflation caused by the indexation of administered prices. Among the administered prices, the electricity tariff is one of the items with the highest weight and that contributes most to the variation of the monitored IPCA. Electricity is one of the most important inputs of the national energy matrix, being present not only in the residences, but also is a primordial input for the other sectors of the economy. The present work aims at analyzing the effects that the variations of the tariff of electric power cause in the IPCA and in the categories of goods and services that compose it during the period of January of 1996 until June of 2015. To understand the behavior of the tariff of energy are estimated their determinants. The analysis of the econometric models are based in the methodology of multivariate time series. Overall, positive energy price shocks lead to an increase in the price variation of most IPCA categories. Increases in electricity tariffs also have a positive impact on the IPCA of monitored prices and services.